THE INFLUENCE OF DIVIDEND POLICY, DEBT POLICY & PROFITABILITY ON THE VALUE OF PROPERTY AND REAL ESTATE COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Lis Setyowati; Galuh Nurcahyo; Abu Darim; Vanda Kristia Gayatri; Ony Thoyib Hadiwijaya; Syamsul Arifin (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study aims to determine the effect of dividend policy, debt policy, and profitability on firm value. The independent variables in this study are dividend policy as measured by the dividend payout ratio, debt policy as measured by the debt to equity ratio, and profitability as measured by return on assets. The dependent variable in this study is firm value as measured by Tobins'q. The sampling technique uses the purposive sampling method, namely the selection of samples using certain criteria. The form of this research is quantitative. The data analysis technique was carried out by multiple linear regression analysis using the SPSS program. The results of this study are dividend policy and profitability have a positive and significant effect on firm value. While the debt policy has no significant effect on firm value.